(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nobody understands the effects of stress more than the engineering students. With the unforgiving requirements, the mind-boggling exams and assignments, the pressure of project deadlines, and the terrorizing professors, among others, the stress level in engineering soars to great heights, to the point that it already breaks the mental health of the students.Stress is only one mental health issue. There is also the severe anxiety due to the pressure to deliver. Engineering students are almost always expected to be on top, but this is challenging to do when they have problems to juggle not only in academics but also in personal life. The performance in college often ends up to just passing which leads to frustration. And there is depression. It’s a serious mental problem that erodes the well-being of engineering students, characterized by low self-esteem, loss of interest in almost all things, and feeling of hopelessness. The course somehow forces this kind of problem to the students because of the difficult circumstances. This is the ultimate case of mental health issues in engineering that sometimes leads to the students committing suicide.in this paper we discuses which type of problem Engineering Students Suffer from Mental Health Problems, Here’s what to do about it.